2001
DOI: 10.1016/s0092-8674(01)00224-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenin Promotes Neurogenesis and Inhibits Glial Differentiation by Independent Mechanisms

Abstract: The mechanisms by which neural stem cells give rise to neurons, astrocytes, or oligodendrocytes are beginning to be elucidated. However, it is not known how the specification of one cell lineage results in the suppression of alternative fates. We find that in addition to inducing neurogenesis, the bHLH transcription factor neurogenin (Ngn1) inhibits the differentiation of neural stem cells into astrocytes. While Ngn1 promotes neurogenesis by functioning as a transcriptional activator, Ngn1 inhibits astrocyte d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
584
1
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(642 citation statements)
references
References 48 publications
44
584
1
9
Order By: Relevance
“…CBP/p300 complexes with the transcription factor neurogenin 2 and the retinoic acid receptor to induce histone acetylation and transcriptionally active chromatin during motor neuron specification [52]. The closely related basic helix-loophelix (bHLH) factor neurogenin 1 (Ngn1) represses gliogenesis through the sequestration of the CBP-Smad1 complex away from astrocyte differentiation genes, such as glial fibrillary acidic protein (GFAP), during neurogenesis [53]. CBP/p300 and Smad1, separately or together, subsequently associate with neurogenin at neural-specific promoters, such as NeuroD, thereby promoting neuronal differentiation [53].…”
Section: Hats During Neural Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…CBP/p300 complexes with the transcription factor neurogenin 2 and the retinoic acid receptor to induce histone acetylation and transcriptionally active chromatin during motor neuron specification [52]. The closely related basic helix-loophelix (bHLH) factor neurogenin 1 (Ngn1) represses gliogenesis through the sequestration of the CBP-Smad1 complex away from astrocyte differentiation genes, such as glial fibrillary acidic protein (GFAP), during neurogenesis [53]. CBP/p300 and Smad1, separately or together, subsequently associate with neurogenin at neural-specific promoters, such as NeuroD, thereby promoting neuronal differentiation [53].…”
Section: Hats During Neural Developmentmentioning
confidence: 99%
“…The closely related basic helix-loophelix (bHLH) factor neurogenin 1 (Ngn1) represses gliogenesis through the sequestration of the CBP-Smad1 complex away from astrocyte differentiation genes, such as glial fibrillary acidic protein (GFAP), during neurogenesis [53]. CBP/p300 and Smad1, separately or together, subsequently associate with neurogenin at neural-specific promoters, such as NeuroD, thereby promoting neuronal differentiation [53]. The posttranslational modifications of CBP and p300 also regulate the functions of these enzymes, and the phosphorylation of CBP through the atypical protein kinase C (aPKCζ) plays a critical role in controlling glial and neuronal differentiation [54].…”
Section: Hats During Neural Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During brain development, NEUROG2 has a specific spatiotemporal expression pattern, because it is exclusively detected in the ventricular zone and only during neurogenesis (Fig 5A) 25. It has been demonstrated that a negative feedback mechanism is essential for the correct transition between the inhibition of neurogenesis and the induction of early gliogenesis 26.…”
Section: Discussionmentioning
confidence: 99%
“…The basic helix-loop-helix (bHLH) transcriptional factors play a major part in this process [2,3], and they can be classified into three types according to their functions [4,5]. Class I, E proteins, including two isoforms of E2A gene product, E12 and E47, are ubiquitously expressed in all tissues and are capable of forming heterodimers with other bHLH proteins [6]; Class II, tissue-specific activators, are involved in cell fate determination, and bind DNA by forming heterodimers with E proteins [7,8]; Class III, negative regulators such as the Id and Hes families, inhibits the Class II bHLH protein activity by interfering with their functional dimerization [9][10][11].…”
Section: Introductionmentioning
confidence: 99%